2014
DOI: 10.1038/nature13522
|View full text |Cite
|
Sign up to set email alerts
|

Interacting supernovae from photoionization-confined shells around red supergiant stars

Abstract: Betelgeuse, a nearby red supergiant, is a runaway star with a powerful stellar wind that drives a bow shock into its surroundings 1-4 . This picture has been challenged by the discovery of a dense and almost static shell 5 that is three times closer to the star than the bow shock and has been decelerated by some external force. The two physically distinct structures cannot both be formed by the hydrodynamic interaction of the wind with the interstellar medium. Here we report that a model in which Betelgeuse's … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 44 publications
1
85
0
Order By: Relevance
“…Externallyphotoionized cool runaway stars that move rapidly in the H II region produced by an other source of ionizing radiation have particularly bright optical emission, see e.g. the cases of the red supergiant Betelgeuse Mackey et al 2014) and IRC−10414 ). These circumstellar structures are themselves sensitive to the presence of even a weak ISM background magnetic field of a few µG (van Marle et al 2014).…”
Section: The Case Of Runaway Cool Starsmentioning
confidence: 99%
“…Externallyphotoionized cool runaway stars that move rapidly in the H II region produced by an other source of ionizing radiation have particularly bright optical emission, see e.g. the cases of the red supergiant Betelgeuse Mackey et al 2014) and IRC−10414 ). These circumstellar structures are themselves sensitive to the presence of even a weak ISM background magnetic field of a few µG (van Marle et al 2014).…”
Section: The Case Of Runaway Cool Starsmentioning
confidence: 99%
“…Bladh et al 2015). The formation mechanism is also fundamentally different from the shells observed around high-mass evolved stars, where photoionization creates confined shells (Mackey et al 2014). Thermal emission from the dust in detached shells was first observed in the far-infrared by IRAS (van der Veen & Habing 1988;Waters et al 1994;Izumiura et al 1997), and more recently by AKARI and Herschel (Kerschbaum et al 2010;Izumiura et al 2011;Cox et al 2012;Mečina et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…WOH G64 in the Large Magellanic Cloud also shows similar nebular emission lines (Levesque et al 2009). Mackey et al (2014) proposed that Betelgeuse's wind is also externally photoionized, to explain the presence of a static neutral shell around the star (Le Bertre et al 2012). We expect on this basis that many red supergiants have photoionized winds.…”
Section: Introductionmentioning
confidence: 99%
“…We expect on this basis that many red supergiants have photoionized winds. Mackey et al (2014) showed that the winds of red supergiants could be decelerated and accumulated into a dense shell, if the wind is exposed to an external ionizing radiation field from all sides. This could have important consequences for the fate of the mass lost during the red supergiant phase, and also for any subsequent evolutionary phases and the observational characteristics of the star's eventual supernova explosion (Mackey et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation